Modulations in neural pathways excitability post transcutaneous spinal cord stimulation among individuals with spinal cord injury: a systematic review - Tajali, Shirin; Balbinot, Gustavo; Pakosh, Maureen; Sayenko, Dimitry G.; Zariffa, Jose; Masani, Kei (Frontiers in Neuroscience, 2024)
Introduction Transcutaneous spinal cord stimulation (TSCS), a non-invasive form of spinal cord stimulation, has been shown to improve motor function in individuals living with spinal cord injury (SCI). However, the effects of different types of TSCS currents including direct current (DC-TSCS), alternating current (AC-TSCS), and spinal paired stimulation on the excitability of neural pathways have not been systematically investigated. The objective of this systematic review was to determine the effects of TSCS on the excitability of neural pathways in adults with non-progressive SCI at any level. Methods The following databases were searched from their inception until June 2022: MEDLINE ALL, Embase, Web of Science, Cochrane Library, and clinical trials. A total of 4,431 abstracts were screened, and 23 articles were included. Results Nineteen studies used TSCS at the thoracolumbar enlargement for lower limb rehabilitation (gait & balance) and four studies used cervical TSCS for upper limb rehabilitation. Sixteen studies measured spinal excitability by reporting different outcomes including Hoffmann reflex (H-reflex), flexion reflex excitability, spinal motor evoked potentials (SMEPs), cervicomedullay evoked potentials (CMEPs), and cutaneous-input-evoked muscle response. Seven studies measured corticospinal excitability using motor evoked potentials (MEPs) induced by transcranial magnetic stimulation (TMS), and one study measured somatosensory evoked potentials (SSEPs) following TSCS. Our findings indicated a decrease in the amplitude of H-reflex and long latency flexion reflex following AC-TSCS, alongside an increase in the amplitudes of SMEPs and CMEPs. Moreover, the application of the TSCS-TMS paired associative technique resulted in spinal reflex inhibition, manifested by reduced amplitudes in both the H-reflex and flexion reflex arc. In terms of corticospinal excitability, findings from 5 studies demonstrated an increase in the amplitude of MEPs linked to lower limb muscles following DC-TSCS, in addition to paired associative stimulation involving repetitive TMS on the brain and DC-TSCS on the spine. There was an observed improvement in the latency of SSEPs in a single study. Notably, the overall quality of evidence, assessed by the modified Downs and Black Quality assessment, was deemed poor. Discussion This review unveils the systematic evidence supporting the potential of TSCS in reshaping both spinal and supraspinal neuronal circuitries post-SCI. Yet, it underscores the critical necessity for more rigorous, high-quality investigations.